Evaluation of Multiple Choice Items in the Telecommunication and Navigation Engineering Department with Validation - Harianto, Bambang Bagus; Wardhono, Arie; Suprianto, Bambang; Suryono, Wiwid (Technium Social Sciences Journal, 2023)
Improved multiple-choice questions (MCQs) item analysis is fundamental to be used for further tests. Besides increasing item analysis can also be used to removes items that are trapped in a test. This journal focuses on the quality of the questions on the test. It explores the relationship between the difficulty index (p-value) and the discrimination index (DI) and the efficiency of the distractor (DE). The research will be conducted by 49 6th semester students currently studying Diploma, especially in air navigation engineering in education at Aviation Polytechnic of Surabaya. Fifty multiple-choice questions will be given while a final exam for the transmission media and antenna courses. The value of validity using the Pearson correlation with a significance level of 5% and reliability using Cronbach's Alpha. We find that the difficulty index (p) is 59% with an SD value of 10%, while the DI value is 30 % with an SD value 10% and DE with a value of 25% (SD 22%) has item items with average difficulty and discriminatory power related to functional impairments that must be integrated into the test later to improve the quality evaluation.